HISTORICAL STUDY ON THE CHANGES OF RELIGIOUS AND MORAL EDUCATION IN INDONESIA (State Islamic University (UIN) of Sunan Ampel Surabaya, 2014)
This historical study answers questions on phases of terms and philosophical changes of religious teaching in Indonesia since 1945-2013. The study shows that the subject’s term from 1945-1950 was Religious Teaching. Meanwhile in 1951, the term was converted into Religious Education. The term religious teaching was judged inappropriatly as its’ orientation only focused on knowledge dimension. However, religious education also covered dimensions of attitude, knowledge, and skills. Therefore, those three dimensions were covered in the term of “education”. Thus, the latest term was continuously used until 2012. The juridical basis that strengthened the term of education were made during that period. The year of 2002-2012 was regarded as a steady phase for the term as the 1945 Convention finally converted the term of teaching into education. In 2013, religious education term was changed into “religious and moral education”. The term change did not mean that “moral education” should stand alone as a separate subject of religious education but moral education must refer to religion.